2017
DOI: 10.1177/1534508417719680
|View full text |Cite
|
Sign up to set email alerts
|

School Readiness as a Longitudinal Predictor of Social-Emotional and Reading Performance Across the Elementary Grades

Abstract: This study is a brief psychometric report examining the Kindergarten Student Entrance Profile (KSEP). Multiple regression models were tested examining associations between kindergarten teachers’ ratings of children’s social-emotional and cognitive readiness during the first month of kindergarten with academic and social-emotional outcomes almost 6 years later. Significant associations ( p < .05) were identified between children’s cognitive readiness at kindergarten entry and reading fluency in Grade 5, as w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 23 publications
1
13
0
Order By: Relevance
“…The school readiness level/assessment tool/questionnaire completed by the teacher, during the first month of kindergarten, was significantly associated with students' reading fluency and various indicators of their social-emotional well-being during Class 5 (Quirk et al, 2017). The five-factor structure which includes self and social development, language and literacy development, language development, cognitive development, mathematical development, physical development, and health which are proposed best fits the data, with greater embodiment and statistical validity (Abdulfattah & Putranta, 2020;Nguyen et al, 2019).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The school readiness level/assessment tool/questionnaire completed by the teacher, during the first month of kindergarten, was significantly associated with students' reading fluency and various indicators of their social-emotional well-being during Class 5 (Quirk et al, 2017). The five-factor structure which includes self and social development, language and literacy development, language development, cognitive development, mathematical development, physical development, and health which are proposed best fits the data, with greater embodiment and statistical validity (Abdulfattah & Putranta, 2020;Nguyen et al, 2019).…”
Section: Discussionmentioning
confidence: 98%
“…Likewise, early mathematics learning is also a classic executive function challenge (Blair & Raver, 2015). However, research by Quirk et al, (2017) shows that there is vulnerability if the demands for fluency in reading at pre-school age become the focal point of school readiness.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Social skills are often included as a part of the concept of school readiness, which incorporates several areas related to the child's educational setting, such as physical development, approach to learning (e.g., curiosity and creativity), cognition, language skills, emotional development, and social skills (Gullo, 2015). Social skills have repeatedly been linked to the child's ability to perform well in school (see e.g., Arnold et al, 2012;Doctoroff et al, 2016;McClelland et al, 2006;Quirk et al, 2017;Ray & Elliott, 2006;Rhoades Cooper et al, 2014;Sparapani et al, 2018;Webster-Stratton & Reid, 2004). Research on social skills and school performance among children points to the importance of early positive development and stability in social skills (Welsh et al, 2001).…”
Section: Childhood Social Skills and School Performancementioning
confidence: 99%
“…Research has shown that a child’s school trajectory is well-established in the early grades (Alexander & Entwisle, 1988; Cook & Coley, 2017), and school readiness has been shown to be a significant factor in school success and achievement (Quirk, Dowdy, Goldstein, & Carnazzo, 2017). School readiness can be viewed as the broad set academic and social–emotional skills that help children succeed in education programs (Curby et al., 2018; Denham, 2006; Duncan et al., 2007; Lin, Lawrence, & Gorrell, 2003; Miller & Goldsmith, 2017).…”
mentioning
confidence: 99%